2009
DOI: 10.1227/01.neu.0000348291.48810.c2
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorial, Extraventricular Choroid Plexus Carcinoma in an Adult

Abstract: CPCa infrequently affects adults. Only rarely does it present as a supratentorial, extraventricular mass. Resection is the mainstay of therapy. Adjuvant radiation and chemotherapy are rational treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…Although meta-analysis of CPC demonstrated that etoposide was the most effective drug, the response rate was only less than half of cases [33]. Several reports demonstrated efficacy of temozolomide for CPTs (Table 1) [7,12]. In two cases of recurrent CPP with craniospinal dissemination treated with temozolomide, one case showed radiographically stable disease for 17 months after surgery, whereas in the other case tumor control failed [7].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although meta-analysis of CPC demonstrated that etoposide was the most effective drug, the response rate was only less than half of cases [33]. Several reports demonstrated efficacy of temozolomide for CPTs (Table 1) [7,12]. In two cases of recurrent CPP with craniospinal dissemination treated with temozolomide, one case showed radiographically stable disease for 17 months after surgery, whereas in the other case tumor control failed [7].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors recommend regional radiation [30] whereas others performed craniospinal radiation [11,24]. Information concerning UC, U138MG cell line as unmethylated control; P, patient's tumor sample; MW, molecular weight marker appropriate doses and extent of radiation needed is still lacking [12,18]. For CPC patients, because dissemination and relapses outside the primary site are likely to occur, craniospinal radiation therapy should be considered, especially in adults who have less risk of intellectual sequelae caused by radiation than do children [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations